Aforizmi in razmišljanja: O pravu in pravnikih - Ivanjko, Šime (2020)
Aphorisms and Reflections: About Law and Jurists. Aphorisms and Reflections is a book about law, lawyers, the study of law, and the role of law in the social environment. It was written by the professor emeritus of the Faculty of Law of the University of Maribor, Šime Ivanjko, Ph.D., who is considered a popular professor, excellent lecturer and top legal expert, writer of scientific and professional works on law, law studies and lawyers - his bibliography includes 1684 units, including more than 60 scientific, professional monographs and textbooks. Prof. Šime Ivanjko, Ph.D., also studied philosophy, so in his book Aphorisms and Reflections, he connects the humanistic and social science views of the world by upgrading fundamental philosophical and rational questions with law. The Introduction presents the theoretical starting points of his aphorisms and reflections; followed by a chapter bringing aphorisms about law and jurists; followed by a chapter in which the author, a lawyer with fifty years of legal practice and a legal expert in the field of economics, reflects on the legal profession, the study of law and its role in society; a special chapter is devoted to a reflection on the legal profession and the position of the lawyer in modern society; the book is accompanied by an extensive interview that the author had in legal review Pravna praksa. The aphorisms are distinguished by the reflections that the author and the professor encouraged among law students during tutorials and during lectures at the Maribor Faculty of Law. The aphorisms are substantively related to (1) Roman legal thinking and thinkers of the Greco-Roman era, (2) the study of law and Maribor students, (3) the role of law in society, (4) the position of a lawyer, (5) the media, (6) ethics and morals and (7) general content that is (indirectly) related to law. It is about thinking about current issues of law and jurists in our society over the last eight years, when the author retired. The aphorisms and reflections point to the author's active attitude towards law and his commitment to enforcing the legal ethos and business morality in modern society. Keywords: lawyer, law, study of law, politics, media, morals
Keywords: lawyer; law; study of law; politics; media; morals